Jarisch-herxheimer reaction in pregnant womanwith syphilis: case report - Grossi, Rinara; Barros, Ana Carolina; Andrade, Ramon; Galvão, Carolina; Reis, Helena; Ferreira, Dennis C; Moraes, Glaucio de; Godefroy, Philippe (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: syphilis is a disease which has been reported since the fifteenth century and still represents a reasonable challenge to public health care sistem. More than 12 million new cases are reported every year, especially in developing countries. With the commerce of penicillin, to which Treponema pallidum is susceptible, the possibility of eradication had been considered true, which however, did not happen. In certain infectious diseases, the first dose of an effective antimicrobial treatment can initiate an inflammatory response in the host. This work presents the case of a pregnant woman, low socioeconomic status, nulllipara, with a dead fetus with 24 weeks, upon receiving therapy for early syphilis, triggered Jarisch-Herxheimer reaction, which occurred at the Hospital for Women Heloneida Stuart, in São João de Meriti, Rio de Janeiro.